Monitoring of Engine Lubrication using Acoustic Emission Technology - Mohd. Fadhlan Mohd. Yusof; Azman Solahuddin (Widyagama University of Malang, 2019)
This research presents the application of Acoustic Emission (AE) sensor to explore the feasibility of an AE signal in the process of monitoring the engine oil viscosity on different condition of mileage during the engine operation. The viscosity experiment was performed in a prior stage of the experiment using four samples of SAE 5W-30 engine oil with the different condition of mileage. On the next occasion, the AE signal was acquired on three cylinders of a four-stroke gasoline engine with a cooling water system which operates using the previous lubricant sample. In this experiment, the AE sensor was bonded on the outside of the engine block and located at the oil filter and oil sump location. It was found that the AE energy value is capable of determining the variant of the engine oil viscosity. The results from this project show that via AE technology proved to be feasible for the development of a real-time lubricant condition monitoring which was believed to be a new technology in the automotive industry.